Eradication of Biofilm Produced by Staphylococcus aureus and Pseudomonas aeruginosa in Wound Infection by Using Proteinase K Enzyme - Estabraq A. Mahdi; Sura S. Hasan (Indian Journal of Forensic Medicine & Toxicology, 2022)
This research is aimed to eradicate the biofilm formed by bacteria causing wound infection through using proteinase K enzyme. For this purpose six different concentrations of proteinase K were used for the degradation of biofilm produced by Staphylococcus aureus and Pseudomonas areuginosa. These two species are the most common abundant bacteria causing infection by biofilm. Each of the concentrations was kept in contact with the pathogenic bacteria for 1, 2 and three hours. After 3 hours of incubation period the concentration (4 µg /ml) resulted in the highest eradication ability against S. aureus biofilm, while the same concentration was no significant in the eradication of Pseudomonas aeruginosa biofilm.